การแสวงหาข้อมูล แรงจูงใจ ทัศนคติ และพฤติกรรมการซื้อเสื้อผ้าของหญิงรักหญิง - ทิพานันท์ สุขุมาลชาติ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Information Seeking , Motivation, Attitude and Clothes Purchasing of Lesbian Consumer has the objectives to : 1) study information seeking, motivation, attitude and clothes purchasing of lesbian consumer 2) study the differential of demographic variables to information seeking, motivation, attitude and clothes purchasing 3) examine the relationship between consumer s information seeking, motivation, attitude and clothes purchasing. Questionnaires were used to collect data from 400 lesbian consumers aged 20 - 55 years, working and living in Bangkok. The data was analyzed statistically using frequency, percentage, mean, Pearson s Product Moment Correlation and One Way ANOVA. The results were the most of the sample are aged 26 - 30 years, bachelor degree or equal, employee and having income 10,001 - 25,000 baths per month. All together, the information seeking is in the moderate level. In details are always information seeking in the moderate level, seeking from internal sources more level and using internet seeking information the most. As a whole, the motivation to clothes purchasing is more level. The second motivation is the quality of products the most level, Modern is more level of the emotional motivations.Besides that, attitude is agreed level. The quality and reasonable price of products is the most agreed level. All about the clothes purchasing is the most level. The samples purchase from the deparlment stores, at the most level, go alone, purchase for self image, purchase average 2 - 3 months/time, every month purchase T-shirt and V-shirt and spend 1,001 - 1,500 bath each time.